Digital Repression and Shrinking Civic Space: A Gendered Computational Socio-Legal Analysis - Fidela Dzatadini Wahyudi; Wahyudi; Angger Dimas Bayu Sadewo; Bayu Dharmala (Sospol, 2026)
Digitalization does not automatically expand political freedom in the public space. On the other hand, in various Southeast Asian countries, technological developments have gone hand in hand with increasing state control over citizen expression and the narrowing of civic space. This article analyzes the phenomenon of digital repression in this context through a socio-legal computational approach by utilizing V-Dem and Our World in Data data, as well as integrating the theoretical frameworks of Nancy Fraser and Donatella della Porta. The results of the quantitative analysis show that the decline in the liberal democracy index and freedom of expression correlate with increased civil vulnerability of women, particularly in private digital spaces that are increasingly legally supervised and controlled. Cyber law in this context not only serves as a regulatory instrument, but also as a form of legal weaponization that reinforces gender inequalities in access to security, social recognition, and political representation. On the other hand, social movements did not experience disappearance, but transformed into a more fluid and fragmented form of network-based digital activism under the pressure of digital authoritarianism. The study concludes that civic space in Southeast Asia is not disappearing, but is undergoing restructuring through the complex relationship between